Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Kelapa Sawit (Studi Kasus Di Kabupaten Pasaman Barat Kecamatan Ranah Batahan) - Naf’an Pangidoan; Devi Andriyani (Jurnal Ekonomi Pertanian Unimal, 2021)
This study aims to analyze the factors that influence the income ofoil palm farmers in Ranah Batahan District, West Pasaman Regency. Thedata used in this research is secondary data. The method used to analyzethe relationship between variables is multiple linear regression analysis.The results showed that work experience, age, working time andproduction had a positive and significant effect on the income of oil palmfarmers in Ranah Batahan District, West Pasaman Regency.Simultaneously, business experience, age, working time and productionaffect the income of oil palm farmers in Ranah Batahan District, WestPasaman Regency